(untitled) (Research, Society and Development, 2021)
Mead is an alcoholic beverage, resulting from the fermentation of honey dilution in water, in the presence of yeast. The diversification of mead can be carried by out addition of fruits and herbs. Yerba mate is a native plant of South America, being widely studied for being an excellent source of phenolic compounds and with high antioxidant capacity. Thus, the objective of this work was to evaluate the influence of addition of yerba mate powder on the physicochemical properties and on the bioactive potential of meads. For this, three formulations of mead were elaborated: (HC): control - without addition of yerba mate; (HF): with the addition of 1% yerba mate in powder leaves submitted to cold aqueous extraction; and (HQ): with the addition of 1% yerba mate in powder leaves submitted to hot aqueous extraction. Musts and meads were evaluated for physical parameters-compounds, color, content of total phenolic compounds, in vitro antioxidant capacity, and the alcohol content of the meads. The addition of yerba mate extracts contributed to increase the acidity of musts and meads. When analyzing the total solids, all after the reduction there is a decrease in fermentation, and an increase in alcohol content. The values regarding the obtainment for the content of total phenolic compounds and for the antioxidant capacity were the highest for those with yerba mate extract, both in the musts in the meads. Thus, the results obtained in this study revealed that mate is an alternative to increase the bioactive potential of mead.